Analytical and Biological Variables Influencing Quantitative Hepatitis C Virus (HCV) Measurement in HIV-HCV Coinfection - Curtis Cooper; Paul MacPherson; William Cameron (Canadian Journal of Gastroenterology)
The present review considers issues pertaining to the precision and variability of quantitative hepatitis C virus (HCV) measurement in general, outlines the characteristics of HCV RNA in HIV-HCV coinfection and evaluates those factors which may affect this measure. The clinical relevance of accurate HCV measurement in HIV-HCV coinfection is discussed.